Quality Higher Education for the Achievement of the Sustainable Development Goals in Venezuela - Pérez Pivat, Helen (2026)
The objective of this article is to analyze the role of Venezuelan universities in achieving the Sustainable Development Goals (SDGs) to propose a framework for priority actions. A qualitative methodology based on a systematic documentary review was employed, consulting specialized databases (Scopus, Web of Science, SciELO, Redalyc, Dialnet y Google Scholar) and analyzing academic sources from the 2015-2025 period. The results reveal a disarticulation between university policies and sustainable development targets, exacerbated by budgetary precariousness, although resilient teaching and outreach initiatives persist. It is concluded that, to strengthen the university’s role as a transformative agent, it is imperative to establish a governance framework centered on sustainability, digitalization, and intersectoral cooperation. These actions will position academia as a strategic axis in the reconstruction of the national social and economic fabric within the framework of the Global Agenda.